Determinants of COVID-19 deaths in the early stage of the pandemic: worldwide panel data empirical evidence / Siew King Ting ... [et al.] - Siew, King Ting; Howe Eng, Tang; Tze, Wee Lai; Li, Li Lau; Lucy Batchy, Gabriel Puem (Universiti Teknologi MARA Cawangan Kedah, 2023)
The COVID-19 pandemic has caused both economic and public health crises in all countries. Thus, the discovery of determinants of COVID-19 deaths at the early stage is important in order to provide a better execution of resources allocation, management and mitigation policies. Using panel data of 182 countries, we aim to examine the relationship between COVID-19 deaths and three independent variables at the early stage of the pandemic from March to July 2020 at six regional and global levels. The results show that there was a positive relationship between total COVID-19 deaths with total confirmed cases and new deaths, while a negative relationship between total COVID- 19 deaths with new confirmed cases in all countries and regions (except the Americas). The European region was the worst affected region as compared to other regions. Several policies are advanced for the improvement of global public health.